The impact of Tai Chi combined with exogenous adjunctive interventions on middle-aged and elderly patients with cognitive and - Mufan Zhang; Yuping Zou; Jiong Luo; Tingran Zhang (Brazilian Journal of Health Review, 2026)
Objective: To evaluate the clinical and neural effects of Tai Chi combined with exogenous adjunctive interventions in older adults with cognitive and neurological impairments. Methods: Following PRISMA guidelines, we searched PubMed, Web of Science, Cochrane Library, and CNKI for controlled trials comparing combined interventions against single, sham, or routine controls. Methodological quality was assessed via PEDro and MINORS scales, followed by narrative synthesis. Results: Nine moderate-to-high quality studies (N=792) were included. (1) Clinically, combined interventions significantly outperformed single therapies in improving global cognition, working memory, executive function, and sleep quality; (2) Mechanistically, the combination induced central pre-activation (LTP-like effects), enhanced cortical hemodynamics and functional connectivity, and downregulated peripheral pathological and neuroinflammatory markers; (3) Efficacy exhibited strong "timing dependence" (e.g., sequential timing optimized sleep regulation) and "subtype specificity" (higher sensitivity in populations with targeted pathological impairments). Conclusion: Combining Tai Chi with exogenous interventions is a safe, multidimensional synergistic neurorehabilitation strategy that remodels the "brain-body" network. Tailoring intervention timing and protocols to specific clinical subtypes can maximize comprehensive cognitive and neurological recovery in aging populations.